Portuguese Version of the Continuing Bonds Scale–16 in a Sample of Bereaved Parents. Issue 3 (2nd April 2020) - Albuquerque, Sara; Narciso, Isabel; Pereira, Marco
Abstract: The aim of this study was to assess the psychometric properties of the Continuing Bonds Scale–16 (CBS-16) in a sample of Portuguese-speaking bereaved parents. The sample comprised 355 parents (mean age: 40.52 years) who completed the CBS-16 as well as measures of grief and posttraumatic growth. The exploratory factor analysis suggested a two-factor structure (internalized and externalized continuing bonds), which was also supported through a confirmatory factor analysis. The CBS-16 presented satisfactory reliability, as well as construct, convergent, and known-groups validities. These results support the use of the CBS-16 as an adequate measure of continuing bonds among bereaved parents.